Biosensor integrated brain-on-a-chip platforms: Progress and prospects in clinical translation - ALARÇİN, EMİNE (My University, 2023)
© 2023 Elsevier B.V.Because of the brain\"s complexity, developing effective treatments for neurological disorders is a formidable challenge. Research efforts to this end are advancing as in vitro systems have reached the point that they can imitate critical components of the brain\"s structure and function. Brain-on-a-chip (BoC) was first used for microfluidics-based systems with small synthetic tissues but has expanded recently to include in vitro simulation of the central nervous system (CNS). Defining the system\"s qualifying parameters may improve the BoC for the next generation of in vitro platforms. These parameters show how well a given platform solves the problems unique to in vitro CNS modeling (like recreating the brain\"s microenvironment and including essential parts like the blood-brain barrier (BBB)) and how much more value it offers than traditional cell culture systems. This review provides an overview of the practical concerns of creating and deploying BoC systems and elaborates on how these technologies might be used. Not only how advanced biosensing technologies could be integrated with BoC system but also how novel approaches will automate assays and improve point-of-care (PoC) diagnostics and accurate quantitative analyses are discussed. Key challenges providing opportunities for clinical translation of BoC in neurodegenerative disorders are also addressed.
Keywords: Tıp; Biyomedikal Mühendisliği; Yaşam Bilimleri; Biyoteknoloji; Kimya; Fizikokimya; Elektrokimya; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyofizik; Biyokimya; Temel Bilimler; Mühendislik ve Teknoloji; Medicine; Biomedical Engineering; Life Sciences; Biotechnology; Chemistry; Physical Chemistry; Electrochemistry; Health Sciences; Fundamental Medical Sciences; Biophysics; Biochemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Mühendislik; Biyoloji ve Biyokimya; Mikrobiyoloji; ELEKTROKİMYA; BİYOFİZİK; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; MÜHENDİSLİK, BİYOMEDİKAL; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); Life Sciences (LIFE); ENGINEERING; CHEMISTRY; BIOLOGY & BIOCHEMISTRY; MICROBIOLOGY; ELECTROCHEMISTRY; BIOPHYSICS; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; ENGINEERING, BIOMEDICAL; Biyomedikal mühendisliği; Fizik Bilimleri; Physical Sciences; Biosensor; Brain-on-a-chip; Integrated biosensors; Microfabrication; Microfluidics; Microphysiological systems; Organ-on-Chip